Conceptions of LGBT Old Age Among a Rural Population: A Prototypical Analysisof Social Representations - Mendes da Silva Sousa, Evair; da Silva Alves, Mateus Egilson; de Lima Bezerra, Igor Eduardo; Fernandes de Araújo, Ludgleydson; Lima Silva, Maria Fernanda; Aguiar Trevia Salgado, Ana Gabriela (Pensando Psicología, 2024)
This study aimed to understand social representations of LGBT old age among residents of a rural coastal community. Thirty-one adults participated, 65% female, 97% Catholic and heterosexual, and 42% working as fishermen. For data collection, the TALP (free word association technique) was used, analyzed with IRaMuTeQ software, employing the prototypical analysis method and based on the theoretical framework of the Structural Approach to Social Representations. The study revealed dualistic representations that incorporate subtle expressions of prejudice and deny the particularities of these elderly individuals, as well as a view of aging as a natural phenomenon common to all but with specific aspects that affect its course in rural areas. The study also highlighted the difficulties faced by the native populations of these communities. Thus, it is anticipated that this research will support new studies on the investigated topic, aiming to promote rights and visibility for LGBT and rural elderly individuals.
Keywords: Aging; Old age; LGBT; Ruralities; Social representations